2006
DOI: 10.1002/pssc.200564678
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence characterization of cubic CdS epilayers

Abstract: PACS 71. 78.55.Et Cubic CdS epilayers were grown on (100) GaAs substrates by hot-wall epitaxy and their photoluminescence (PL) characteristics were studied. A heavy hole free exciton peak was observed even at room temperature and a light hole free exciton peak was observed at 30 -100 K. The temperature dependence of the free excitonic emission intensity was demonstrated using a two-step quenching mechanism. The excitation power dependence showed that the PL peak at 2.367 eV is due to the free-to-bound tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A similar increase in the low-energy surface state emission intensity upon cooling was reported earlier 33 and assigned to defects and irregularities in the samples. For the cubic phase of CdS, 34 the opposite behavior was reported, where sample cooling caused narrowing of the photoluminescence peaks along with a blue shift.…”
Section: Resultsmentioning
confidence: 99%
“…A similar increase in the low-energy surface state emission intensity upon cooling was reported earlier 33 and assigned to defects and irregularities in the samples. For the cubic phase of CdS, 34 the opposite behavior was reported, where sample cooling caused narrowing of the photoluminescence peaks along with a blue shift.…”
Section: Resultsmentioning
confidence: 99%
“…The pure cubic CdS spectrum has been discussed in detail elsewhere. 11,12,40 In spite of very low Mn composition of x = 0.020 and 0.030, no other peaks such as an appreciable near-edge emission peak and SA peak, shown in the pure CdS PL spectrum, were observed in the higher energy region of 2.2 to 2.5 eV. Only one broad and strong emission peak labeled as A was observed.…”
Section: Resultsmentioning
confidence: 59%
“…It is found that with temperature increasing, the PL peak intensity decreases slowly below 50 K, while exponentially after that till 300 K. This phenomenon suggests that there exist two different non-radiative recombination paths in as-prepared CdS:CdO/Si-NPA, which independently lead to the PL quenching in different temperature ranges. [24] By taking into account a two-step quenching mechanism, the PL intensity as a function of temperature can be expressed as [24] 𝐼(𝑇…”
mentioning
confidence: 99%
“…This suggests that the PL quenching occurring at the low temperature range (below 50 K) should be attributed to the thermally activated transition between the heavy hole and the light hole, with an energy requirement of ∼10-12 meV. [24,27] Beyond 50 K, the main non-radiative process responsible to the PL quenching might be due to the thermal escape from the structural defects assisted by scattering with longitudinal optical (LO) phonons. [23] According to the fitted value (Table 1), the activation energy is ∼66.7 meV.…”
mentioning
confidence: 99%